Magnetohydrodynamic Three-Dimensional Flow and Heat Transfer over a Stretching Surface in a Viscoelastic Fluid - Ahmad, Kartini; Nazar, Roslinda (Journal of Science and Technology, 2011)
In this paper, the problem of steady laminar three-dimensional magnetohydrodynamic (MHD) boundary layer flow and heat transfer over a stretching surface in a viscoelastic fluid is investigated. The equations which govern the flow are coupled nonlinear ordinary differential equations, which are solved numerically using a finite-difference scheme known as the Keller-box method. Various physical governing parameters such as the magnetic parameter M, the material or viscoelastic parameter K and the Prandtl number Pr are considered and the effects of these parameters are investigated. It is found that the material parameter K and the magnetic parameter M present opposite effects on the fluid flow and heat transfer characteristics. The numerical results obtained for the skin friction coefficient and the local Nusselt number are presented in tables. The features and profiles of the flow and heat transfer characteristics are illustrated in the forms of graphs.